آراء السياسة الشرعية عند عبد الرزاق السنهوري و تقي الدين النبهاني - Anas, Muhammad Khoirul; Sujoko, Imam (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
The subject of Islamic politics is of utmost importance in building Islamic civilization, ancient and modern. Mistakes in understanding legitimate politics are a great problem in our society today. Abd al-Razzaq al-Sanhuri and Taqi al-Din al-Nabhani had understandings, opinions, values, and experience in building Islamic civilization. We benefit from studying and comparing them for a correct understanding of the subject of islamic politics. The political crisis that occurred within some countries or their international relations needs solutions, and to know how to implement Sharia politics and the method of applying it in the present era in which many diverse political ideas have spread, Muslims should know the concept of Sharia politics and the opinions of scholars about it, which is the result of thinking and understanding. Conscious and rational in its topics, including the issue of authority or the legitimate political institution, which in our time is now called the state. This research aims to know the concept of Sharia politics, especially with Abd al-Razzaq al-Sanhuri and Taqi al-Din al-Nabhani, then know its personality and contributions to building the civilization of the nation, as well as knowing the aspects of agreement and differences between the views of Sharia politics with Abd al-Razzaq al-Sanhuri and Taqi al-Din al-Nabhani.